2011
DOI: 10.1007/s11089-011-0373-4
|View full text |Cite
|
Sign up to set email alerts
|

Normative MMPI-2 Profiles of Christian Counseling Students: An Investigation of Subculture in Standardized Testing

Abstract: This research sought to explore whether a normative profile on the MMPI-2 emerged for counseling students in a counselor training program at a seminary in the Midwest and the extent to which this profile compares to those proposed for counseling students or those preparing for pastoral ministry. Normative profiles of master's level counseling students were compared to profiles of similar samples. Findings indicated that profiles of the current student sample are similar to those of other religious students. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Two authors did not respond and their published articles did not clarify the issue (Cardwell, 1996; Greene, 2007). Two authors (Duris et al, 2007; Marlett, Wetherbee, & Donofrio, 2012) reported that they did not apply decision rules to identify invalid profiles. One author (Gamino et al, 2007) reported that invalid profiles were identified and excluded, but their decision rules also identified elevated L scales.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two authors did not respond and their published articles did not clarify the issue (Cardwell, 1996; Greene, 2007). Two authors (Duris et al, 2007; Marlett, Wetherbee, & Donofrio, 2012) reported that they did not apply decision rules to identify invalid profiles. One author (Gamino et al, 2007) reported that invalid profiles were identified and excluded, but their decision rules also identified elevated L scales.…”
Section: Resultsmentioning
confidence: 99%
“…Assignment of participant status was possible for all but one study (Cardwell, 1996). After excluding the Cardwell study because of its indeterminant status, Gamino et al (2007) and Greene (2007) due to the issue of an exclusionary rule for invalid profiles, and Knabb et al (2011) due to its outlier status, this left five publications identified as assessing applicants (Marlett et al, 2012; Plante et al, 2003; Plante & Apodaca, 2011; Plante et al, 1996; Rosik et al, 2012); two reporting on volunteer nonapplicants (Duris et al, 2007; Putnam et al, 1996); and one assessing a group of clergy charged with sexual abuse (Plante & Aldridge, 2005). A moderator analysis of L scale scores for applicant ( n = 5) and nonapplicant ( n = 2) studies demonstrated a larger effect size for the former, and approached significance (trued¯ for applicants = 0.60; trued¯ for nonapplicants = 0.30; p = .052 for the difference).…”
Section: Resultsmentioning
confidence: 99%
“…Other occupations for which the MMPI or MMPI-2 has demonstrated efficacy for employee selection include nuclear power plant operators (e.g., Kelley, Jacobs, & Farr, 1994), military personnel (e.g., Staal, Cigrang, & Fiedler, 2000;Xiao et al, 2011), clergy (e.g.. Plante, Aldridge, & Louie, 2005), pastoral counselors (Marlett et al, 2012), and hospital administrators (Thumin, 2002).…”
Section: Mmpi-2 and Performance Researchmentioning
confidence: 99%
“…Although the MMPI was originally developed for assessment of clinical populations, the MMPI-2 was normed on a nonclinical sample. One of its current uses is screening applicants for sensitive occupations such as clergy, law enforcement, and military (e.g., Plante & Boccaccini, 1998; Reaves, 2010; Rosik, Renteria, & Pittman, 2012; Xiao, Han, & Han, 2011), or for training programs in medicine, psychology, and the seminary (e.g., Butcher, Ones, & Cullen, 2006; Marlett, Wetherbee, & Donofrio, 2012). These occupations can be associated with high stress, personal risk, and a high degree of personal responsibility (Butcher, 1991).…”
Section: Mmpi-2 and Performance Researchmentioning
confidence: 99%
See 1 more Smart Citation